Characterization and Performance Nanofiltration Membranes in Water Quality for Goldfish (Carassius auratus) Aquaculture - Utari, Inpita Casuarina Eqisetia; Yanuhar, Uun; Hertika, Asus Maizar Suryanto; Suryanto, Heru; Maulana, Jibril; Caesar, Nico Rahman; Ismail, Mahrus (Universitas Negeri Malang, 2024)
Water quality is an important factor in aquaculture activities, including goldfish (Carassius auratus) farming. One approach to improving water quality is the use of nanofilters. This study aims to evaluate the performance of nanofilters made from Sargassum sp. with the addition of copper oxide nanoparticles. The method used involves the fermentation of bacterial cellulose from Acetobacter xylinum using Sargassum sp. extract as a medium, followed by homogenization and the addition of CuO-NPs at concentrations of 0.5%, 1%, and 1.5%, and subsequent oven drying. The nanofilter membrane will then be analyzed using SEM, XRD, and FTIR to characterize its properties. Performance tests will assess the quality of water used in goldfish farming, including pH, TOM, TDS, and TSS after treatment with the nanofilter. Morphological results show a rougher and denser surface with dispersed CuO-NPs. Characterization reveals cellulose I with crystallinity values ranging from 86.80% to 90.20%, with functional group peaks at 3145, 2927, and 1735 cm⁻¹ indicating cellulose characteristics, and a peak at 424 cm⁻¹ indicating Cu-O bonds. Statistical analysis of performance tests on the water quality of goldfish farming in the F-test shows significant differences (p